2014
DOI: 10.1089/cyber.2013.0492
|View full text |Cite
|
Sign up to set email alerts
|

Does Screen Size Matter for Smartphones? Utilitarian and Hedonic Effects of Screen Size on Smartphone Adoption

Abstract: This study explores the psychological effects of screen size on smartphone adoption by proposing an extended Technology Acceptance Model (TAM) that integrates an empirical comparison between large and small screens with perceived control, affective quality, and the original TAM constructs. A structural equation modeling analysis was conducted on data collected from a between-subjects experiment (N = 130) in which users performed a web-based task on a smartphone with either a large (5.3 inches) or a small (3.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 52 publications
5
81
0
Order By: Relevance
“…This could be optimal for the WEBMICROSCOPE ® server, using its high-quality images (Fleming et al 2016;Sanchez-Franco 2010). Although larger smartphone screens will lead to a greater perceived control of the subjects (Kim and Sundar 2014), bigger is not always convenient for use in students' everyday lives, which might explain the phenomenon noted above. Tablets and desktops (91% of the total accesses from outside the UEF EDUROAM network) might appeal to both task-and affect-oriented needs when studying histology.…”
Section: Discussionmentioning
confidence: 99%
“…This could be optimal for the WEBMICROSCOPE ® server, using its high-quality images (Fleming et al 2016;Sanchez-Franco 2010). Although larger smartphone screens will lead to a greater perceived control of the subjects (Kim and Sundar 2014), bigger is not always convenient for use in students' everyday lives, which might explain the phenomenon noted above. Tablets and desktops (91% of the total accesses from outside the UEF EDUROAM network) might appeal to both task-and affect-oriented needs when studying histology.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, perceived usefulness had no explanatory power [55]. For general consumer goods, which are difficult to divide into hedonic and utilitarian products, enjoyment provided meaningful explanatory power in the adoption decisions of customers [56,57]. In those cases, perceived ease of use remained statistically important as a utilitarian evaluation factor [52,54,58].…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Prior studies (Joo & Sang, 2013; K. J. Kim & Sundar, 2014;Y. Park & Chen, 2007;Tsai & Ho, 2013) also found that perceived ease of use encourage consumers' to purchase a smartphone.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Other innovative product features (Çakır & Demir, 2014;Joo & Sang, 2013; K. J. Kim & Sundar, 2014;Osman, Talib, et al, 2011; Ömürbek & Şimşek, 2012; Puad, Yusof, & Sahak, 2016Tan, Yeh, Chen, Lin, & Kuo, 2012;Tan, Yi-Der Yeh, Lin, & Kuo, 2012;Tsai & Ho, 2013)were also found to be decisive on purchase intention. One study (Böhm, Adam, & Farrell, 2015) have unveiled the significant role of operating systems on smartphone purchase decisions.…”
Section: Literature Reviewmentioning
confidence: 99%